The Relationship between the Frequency of Baby Massage and the Pattern of Defecation of Babies who are Exclusively Breastfed at Bunda Patimah Primary Clinic - Debora Paninsari; Cecilia Arnas B Harefa; Gebby S. A. Tarigan; Yenti Kusnani Duha; Minda Silvia S. Hasibuan; Chiou Feng Lin (STRADA : Jurnal Ilmiah Kesehatan, 2022)
Baby massage is a stimulus that has many benefits for the growth and development of babies. One of them is to facilitate the digestive system in babies, so babies who often receive massage therapy rarely experience digestive problems and have a good pattern of defecation. The purpose of this study was to determine the relationship between the frequency of infant massage and the pattern of defecation of infants who were exclusively breastfed. The research method used is quantitative research with a cross sectional research design. The number of samples in this study were 40 respondents. The results of the research conducted using the Chi-Square statistical test was p= 0.036<0.05, meaning that both variables had a statistically significant relationship between the frequency of infant massage and the pattern of defecation.